Programme for environmentally sustainable land use planning and settlement development in the OECS - Marshall, Dawn (UNCHS/UNDP Sustainable Land Use Project BridgetownBB)
Provides an overview of the programme which has as its developmental objective to achieve a rational and sustainable utilization of land and related natural resources of the OECS island states through restructured integrated development planning techniques and institutional arrangements.